Probability in the philosophy of religion - Chandler, Jake.; Harrison, Victoria S. (Oxford : Oxford University Press, 2012)
These essays show that philosophy of religion is fertile ground for the application of probabilistic thinking. The authors examine central topics in the field: the status of evidence relating to the question of the existence of God; the rationality of religious belief; and the epistemic significance of religious disagreement.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Religion -- Philosophy; Probabilities